2010
DOI: 10.1073/pnas.0911806107
|View full text |Cite
|
Sign up to set email alerts
|

Human antibodies reveal a protective epitope that is highly conserved among human and nonhuman influenza A viruses

Abstract: Influenza remains a serious public health threat throughout the world. Vaccines and antivirals are available that can provide protection from infection. However, new viral strains emerge continuously because of the plasticity of the influenza genome, which necessitates annual reformulation of vaccine antigens, and resistance to antivirals can appear rapidly and become entrenched in circulating virus populations. In addition, the spread of new pandemic strains is difficult to contain because of the time require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 39 publications
(34 reference statements)
3
109
0
Order By: Relevance
“…A study using mouse MAbs showed that, in addition to anti-HA antibodies, NA-and nucleoprotein-specific MAbs mediated CDL of influenza virus-infected target cells, but matrix protein 1-specific MAbs did not (25). Recently Grandea et al reported that human MAbs specific to an epitope on the highly conserved ectodomain of matrix protein 2 (M2) were able to mediate CDL of CHO cells stably expressing M2 (6). M2 is known to be expressed abundantly at the cell surface (10).…”
mentioning
confidence: 99%
“…A study using mouse MAbs showed that, in addition to anti-HA antibodies, NA-and nucleoprotein-specific MAbs mediated CDL of influenza virus-infected target cells, but matrix protein 1-specific MAbs did not (25). Recently Grandea et al reported that human MAbs specific to an epitope on the highly conserved ectodomain of matrix protein 2 (M2) were able to mediate CDL of CHO cells stably expressing M2 (6). M2 is known to be expressed abundantly at the cell surface (10).…”
mentioning
confidence: 99%
“…Protection induced by M2e-based vaccines such as M2e displayed on recombinant virus-like particles is mediated by antibodies (11) and, like the in vitro broadly neutralizing HA stalk-specific antibodies (16), depends on activating Fc␄ receptors (11,16,17). In line with this, passive transfer of mouse and human monoclonal antibodies directed against M2e can protect against influenza A virus challenge (11,(18)(19)(20)(21). It has also been reported that treatment of experimentally challenged human volunteers with a human monoclonal antibody directed against M2e reduces viral replication and clinical symptoms (22).…”
mentioning
confidence: 82%
“…Similarly, Vella et al reported that adult subjects who received the A/Victoria/3/75(H3N2) inactivated influenza vaccine showed a significant rise in ADCC specific immune lysis (SIL) and developed ADCC antibody titers similar to naturally infected subjects (27). Grandea et al found that monoclonal antibodies derived from healthy subjects, which recognized a highly conserved epitope within the ectodomain of the influenza matrix 2 protein, protected mice from lethal challenge with H5N1 and A(H1N1)pdm09 influenza virus strains, with in vitro evidence suggesting that ADCC and/or CDL antibodies mediated this protection (6). A recent paper by Dilillo et al demonstrated that Fc-FccR interactions are required for stalk-specific, but not globular head-specific, monoclonal antibody-mediated protection during in vivo challenge in mice, suggesting a role for ADCC in protection against influenza via stalk-specific antibodies (2).…”
Section: Introductionmentioning
confidence: 99%